Tr1-Like T Cells – An Enigmatic Regulatory T Cell Lineage - White, Anna Malgorzata; Wraith, David C. (Frontiers in Immunology, 2016)
The immune system evolved to respond to foreign invaders and prevent autoimmunity to self-antigens. Several types of regulatory T cells facilitate the latter process. These include a subset of Foxp3− CD4+ T cells able to secrete IL-10 in an antigen-specific manner, type 1 regulatory (Tr1) T cells. Although their suppressive function has been confirmed both in vitro and in vivo, their phenotype remains poorly defined. It has been suggested that the surface markers LAG-3 and CD49b are biomarkers for murine and human Tr1 cells. Here, we discuss these findings in the context of our data regarding the expression pattern of inhibitory receptors (IRs) CD49b, TIM-3, PD-1, TIGIT, LAG-3, and ICOS on Tr1-like human T cells generated in vitro from CD4+ memory T cells stimulated with αCD3 and αCD28 antibodies. We found that there were no differences in IR expression between IL-10+ and IL-10− T cells. However, CD4+IL-10+ T cells isolated ex vivo, following a short stimulation and cytokine secretion assay, contained significantly higher proportions of TIM-3+ and PD-1+ cells. They also expressed significantly higher TIGIT mRNA and showed a trend toward increased TIM-3 mRNA levels. These data led us to conclude that large pools of IRs may be stored intracellularly; hence, they may not represent ideal candidates as cell surface biomarkers for Tr1-like T cells.